PELATIHAN BERHITUNG CEPAT DENGAN METODE JARIMATIKA DI MTSN 1 PROBOLINGGO - Syadidul Itqan; Lilik Nur Susilowati; Sindi Aulia; Wulan Lailatul Mufidah; Imroatul Ma’rufah; Ika Rizqiyanti; Diana Putri (IEC: Journal of Educational Innovation, 2025)
Multiplication is a fundamental topic in mathematics learning that often presents challenges for students, particularly in achieving speed and accuracy in calculations. This issue was identified among ninth-grade students at MTsN 1 Probolinggo, where learning practices were found to be less engaging and insufficient in supporting students’ conceptual understanding. To address this problem, this community service activity implemented the Jarimatika method as an innovative instructional approach to improve students’ multiplication skills. Jarimatika employs concrete and kinesthetic visualization through the use of fingers, which is suitable for the cognitive characteristics of junior secondary school students. The activity was conducted through three main stages: needs-based planning, participative training, and game-based evaluation. During the participative training stage, students actively practiced multiplication techniques using Jarimatika under guided instruction, while the game-based evaluation aimed to reinforce speed and accuracy in a positive and competitive learning atmosphere. The results demonstrated that students experienced greater ease in performing multiplication operations and showed high levels of enthusiasm and active participation throughout the learning process. Although quantitative measurements were not employed, qualitative observations indicated improvements in students’ confidence, responsiveness, and engagement in mathematics learning. These findings suggest that the Jarimatika method is effective in creating an interactive and enjoyable learning environment and has strong potential to enhance students’ motivation and learning outcomes in mathematics.